Point Pattern Matching Algorithm for Planar Point Sets under Euclidean Transform - Xiaoyun Wang; Xianquan Zhang (Journal of Applied Mathematics)
Point pattern matching is an important topic of computer vision and pattern recognition. In this paper, we propose a point pattern matching algorithm for two planar point sets under Euclidean transform. We view a point set as a complete graph, establish the relation between the point set and the complete graph, and solve the point pattern matching problem by finding congruent complete graphs. Experiments are conducted to show the effectiveness and robustness of the proposed algorithm.